THE EFFECT OF PERCEIVED ORGANIZATIONAL SUPPORT AND JOB SATISFACTION TOWARD INTENTION TO LEAVE OF PLAZA BANGUNAN & ELECTRONIC CALACA, MANADO - Irfanto, Riman; Pandowo, Merinda (FEB Universitas Sam Ratulangi Manado, 2015)
In the present days? competition in the home appliance market are very strong between each other. For a company to survive, they require employees to be able to bring a competitive advantage to their company. Employees is one of the resources that needs to make company exist. The purpose of this research is to find the effect of perceived organizational support and job satisfaction toward employee?s intention to leave at Plaza Bangunan & Electronic Calaca, Manado. This research is a causal research and using quantitative approach. The data was taken using questionnaire to 59 respondents which are the employee of Plaza Bangunan & Electronic Calaca, Manado by using saturated sampling method. Multiple regression analysis method is applied in this research. Research result shows that perceived organizational support and job satisfaction have significant negative effect on intention to leave simultaneously, and also perceived organizational support has significant negatif effect on intention to leave partially with job satisfaction has significant negatif effect on intention to leave partially. As the recommendation, it is better for the company to keep a good quality of their organizational suppport and maintain the satisfaction for the employees. Keywords: organizational support, job satisfaction, intention to leave.